2021
DOI: 10.1109/tcomm.2021.3089476
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Objective Optimization for UAV-Assisted Wireless Powered IoT Networks Based on Extended DDPG Algorithm

Abstract: This paper studies an unmanned aerial vehicle (UAV)-assisted wireless powered IoT network, where a rotarywing UAV adopts fly-hover-communicate protocol to successively visit IoT devices in demand. During the hovering periods, the UAV works on full-duplex mode to simultaneously collect data from the target device and charge other devices within its coverage. Practical propulsion power consumption model and non-linear energy harvesting model are taken into account. We formulate a multi-objective optimization pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(62 citation statements)
references
References 32 publications
0
62
0
Order By: Relevance
“…A singlepolicy MORL aims to optimize one policy for a given preference. For example, the authors in [31] extended a single-objective DDPG to a single-policy MORL to optimize the data rate, total harvested energy, and UAV's energy consumption. However, a single-policy MORL cannot output multiple optimal policies after a run, each of which optimizes a certain preference.…”
Section: Analysis and Motivationmentioning
confidence: 99%
“…A singlepolicy MORL aims to optimize one policy for a given preference. For example, the authors in [31] extended a single-objective DDPG to a single-policy MORL to optimize the data rate, total harvested energy, and UAV's energy consumption. However, a single-policy MORL cannot output multiple optimal policies after a run, each of which optimizes a certain preference.…”
Section: Analysis and Motivationmentioning
confidence: 99%
“…In addition, recent research looks on multiobjective optimization of UAV-assisted communication [48,49]. Over the course of a flight, a multiobjective optimization problem is constructed to jointly optimize three objectives [49]: (1) maximization of cumulative data rate, (2) maximization of total gathered energy, and (3) reduction of UAV energy consumption.…”
Section: Related Workmentioning
confidence: 99%
“…In addition, recent research looks on multiobjective optimization of UAV-assisted communication [48,49]. Over the course of a flight, a multiobjective optimization problem is constructed to jointly optimize three objectives [49]: (1) maximization of cumulative data rate, (2) maximization of total gathered energy, and (3) reduction of UAV energy consumption. Because these goals are incompatible, the authors suggested an enhanced deep deterministic policy gradient (DDPG) technique for learning UAV control policies with multiple goals.…”
Section: Related Workmentioning
confidence: 99%
“…In recent works, effectiveness of FD in a UAV network was shown in [19], where the authors considered maximizing the DL sum rate while maintaining the minimum quality-ofservice (QoS) for the UL users, by optimizing the resources and location of the UAV. In [20], FD was considered in a UAV-assisted wireless powered Internet-of-Things (IoT) network, where the FD UAV collects data from the target IoT device and simultaneously charges remaining devices utilizing fly-hover-communicate protocol. Moreover, a FD UAV relay network was considered in [21], to jointly optimize the HD UL and DL users scheduling, and the UAV trajectory.…”
Section: Introductionmentioning
confidence: 99%
“…The optimization problem is non-convex and non-tractable. MOOP was also considered in [20], where a deep learning approach is used to solve the conflicting system objectives. Contrary, we first adopt weighted Tchebycheff method to convert MOOP to a single-objective-optimization-problem (SOOP).…”
Section: Introductionmentioning
confidence: 99%